Understanding the Logic of Iqna‘i Through the Inspirational Story of Prophet Ibrahim in Tafsir Mafātiḥ al-Ghayb - Rofi'i, Muhammad Arwani; Arrois, Syaiful Makhi Ula; Hamzah, Muhammad Habibi; Saleh, Sujiat Zubaidi (QOF, 2024)
This study examines the concept of persuasive reasoning (iqna‘i) in the Qur’an, focusing on the narrative of Prophet Ibrahim as interpreted in Tafsir Mafātiḥ al-Ghayb. As a form of deductive reasoning, iqna‘i logic strengthens faith and resilience in the face of trials. The study addresses the gap between the classical narratives of prophetic stories and their relevance to contemporary readers, emphasizing the importance of actualizing the timeless values inherent in these accounts. This study used a qualitative approach by analyzing tafsir, hadith, and related literature to examine the context and implications of Prophet Ibrahim’s use of iqna’i reasoning. His logical approach, characterized by unwavering obedience to Allah, trust in divine plans, steadfastness, courage, and monotheistic teachings, reinforced his faith and resilience during divine tests. This study contributes to understanding iqna’i logic within the Qur’anic framework by offering a concrete example through the story of Prophet Ibrahim. In conclusion, through an in-depth analysis of the story of the Prophet Ibrahim, this article has shown the relevance and actual application of the logic of iqna’i in everyday life, enriching Islamic understanding and inspiring readers to face challenges more confidently.